Manufaktur Alat Pengolah Limbah Plastik Menjadi Bahan Bakar Alternatif (Minyak Solar) dengan Metode Pirolisis - Jupri Yanda Zaira Zaira; Darwis Dani; Roni Novison; Agus Wijianto; M. Refky Hasibuan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Pyrolysis is a thermochemical process that can break down organic/inorganic materials into more valuable compounds by heating them to high temperatures. In this research, a laboratory-scale plastic waste pyrolysis system was manufactured, designed using CAD software, with all material components and the heating system selected. The pyrolysis unit consists of a stainless-steel reactor tube as the main component with a diameter of 0.5 m and a height of 1.5 m, an LPG-based heating system, and a galvanic condensation tube to convert vapor into pyrolysis oil. The manufacturing process involved fabricating the reactor tube using Shielded Metal Arc Welding (SMAW) with a 2.6 mm-diameter E6013 electrode. The testing was conducted at temperatures ranging from 300 to 400°C, with a capacity of 10 kg of polyethylene (PE) and polypropylene (PP) plastic per cycle. During the initial phase, leaks were found at the pipe joints and reactor lid, but repairs using heat-resistant sealing adhesive successfully restored the device to proper function. The outcome of this research is the creation of a pyrolysis unit capable of converting plastic waste into a primary product, pyrolysis oil. Each cycle, with a plastic waste capacity of 10 kg, can produce approximately 4.5 liters of pyrolysis oil, along with pyrolysis gas and solid residue. The produced pyrolysis oil has a calorific value of approximately 462 kJ/kg, which is close to that of fossil fuels (diesel oil), with a density of 0.83- 0.85 g/cm³.